A new deep-sea species of Epimeria Costa in Hope, 1851 (Amphipoda, Amphilochidea, Epimeriidae) from off southwestern Mexico - Winfield, I.; Hendrickx, M.e. (Zootaxa, 2020)
A single ovigerous female specimen of a new species of Epimeria Costa in Hope, 1851 was collected from deep sea, off southwestern Mexico, in the eastern Pacific. Epimeria karamani sp. nov., is most similar to females of E. cora J.L. Barnard, 1971, E. pacifica Gurjanova, 1995 and Epimeria morronei Winfield, Ortiz & Hendrickx, 2013. However, it differs from these species by: eyes long and slightly kidney-shaped; pleonite 3 strongly carinate, with dorsal tooth produced and acute; urosomite 1 with a wide mid-dorsal notch and a strong, upright blunt tooth; coxa 3 anterior margin slightly truncate and with two processes marginally; coxa 4 ventral margin linear, with facial granules and simple setae; gnathopods palm with distal bifid setae; telson straight medially, distal margin crenulate and with minute setae. The new species described herein increases the number of Epimeria species from the Pacific Ocean to 14, and from the eastern Pacific to three.